Impact of Inpatient Automatic Therapeutic Substitutions on Postdischarge Medication Prescribing. Issue 9 (October 2017) - Shah, Pooja J.; Cruz, Jennifer L.; Pappas, Ashley L.; Waldron, Kayla M.; Savage, Scott W.
Background: Automatic therapeutic substitution (ATS) is the act of therapeutic interchange, in which patients are transitioned from a nonformulary preadmission medication to an equivalent formulary medication upon admission. ATS protocols are able to provide several benefits; however, if medications are unreconciled at the time of discharge, then use may lead to duplication or omission resulting in adverse outcomes. The objective was to assess the impact of preidentified ATS protocol use during admission on duplication and omission postdischarge.Methods: This study included adults who received a preidentified ATS upon admission. The primary outcome was the incidence of duplication or omission at the time of discharge. The secondary outcome was the incidence of duplication or omission at the time of discharge in moderate-to-high readmission risk patients with completed transitions of care (TOC) services compared with incomplete TOC services.Results: A total of 689 encounters were assessed for appropriate reconciliation, duplication, or omission at time of discharge. The incidence of duplication or omission at the time of discharge was 9% (n = 62). Of the 689 encounters, 287 were assessed for the secondary outcome. The rate of duplication or omission at the time of discharge was 10% (n = 19) in the complete TOC services group and 8% (n = 8) in the incomplete TOC services group (P = .6763).Conclusion: This study identified a high rate of appropriate reconciliation of ATS protocols at the time of discharge, which illustrates ATS protocols are a safe medication use management strategy if implemented as intended.